How to Harvest The Radial Forearm Free Flap - Atmodiwirjo, Parintosa; Ramadan, Mohamad Rachadian; Triatmoko, Sara Ester; Ralena, Nadhira Anindita (Lingkar Studi Bedah Plastik Foundation, 2020)
Summary: Radial forearm flap is fasciocutaneous flap from the volar aspect of the forearm that based on the perforator of radial artery. Radial forearm free flap (RFFF) has several advantages and disadvantages. It has unique characteristic of thin and pliable tissue. It may be indicated when a defect requires a thin flap with little bulk of soft tissue or multiple skin islands are needed to be provided. Physical signs and symptoms of poor peripheral digit perfusion or healing contraindicate the harvest of the radial artery pedicle. Preparations for RFFF procedure include history taking, physical examinations and supporting examinations. Several steps of intraoperative preparations should also be conducted.